Characterization of Pvc-Tetraruthenated Metalloporphyrins Modified Electrodes: Application as Electrocatalyst in the Nitrite Reduction - Aguirre-Quintana, M; Aguirre-Quintana, M (Wiley-VCH Verlag, 2011)
This paper describes the electrochemical reduction of nitrite ion in 0.1 M NaClO4, on glassy carbon or ITO electrodes modified with mixtures PVC- tetraruthenated metalloporphyrins. This electrode is able to keep the extraordinary electrocatalytic properties of the macrocycle allowing multielectronic transfers and a great stability as a consequence of the inclusion of the macrocycles into a polymeric support such as PVC. On the other hand, the electrochemical reduction of nitrite ion on these modified electrodes studied by cyclic voltammetry shows an enhancement in the current values and lower overpotential compared with the activity of the bare glassy carbon electrode. Controlled potential electrolysis experiments verify the production of ammonia, hydrazine and hydroxylamine, showing the electrocatalytic character and the stability of this modified electrode. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.